Corrosion Fatigue Study of 6061 Aluminum Alloy: The Effect of Coatings on the Fatigue Characteristics - Chanyathunyaroj, Kittisak; Moonrin, Nakarin; Laungsopapun, Ghit; Phetchcrai, Sompob (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2022)
This study proposes a method for protecting 6061 aluminum alloy from corrosion fatigue. Corrosion fatigue can reduce fatigue strength at the endurance limit (10 8 cycles) from 55 pct yield tensile strength (YTS) to less than 30 pct YTS. This study revealed that anodizing and powder coating, which are commonly used in industry to prevent base metal corrosion, do not protect against damage from corrosion fatigue. Introduction of electrodeposition after anodizing was found to improve the resistance to corrosion fatigue. Electrodeposition increased the fatigue lives of anodized specimens in both ambient and corrosive environments.